Factors associated with oral Candida colonization in neonates at intensive care unit - I Putu Wijana; Hendra Santoso; I Made Swastika (Paediatrica Indonesiana, 2004)
Background Oral candidiasis still has high prevalence andfrequently causes problems in the neonatal period.Objective To evaluate some factors associated with the occurrenceof oral Candida colonization in neonates.Methods A cross sectional study was performed at the IntensiveCare Unit, Neonatology Division, Department of Child Health,Medical School, Udayana University/Sanglah Hospital Denpasar,from November 2002 to April 2003. Eighty neonates were enrolled.Oral mucous swabs were obtained and examined for Candidacolonization using potassium hydroxide (KOH). Data were analyzedby prevalence ratio and logistic regression; a p value of <0.05 wasconsidered significant.Results The prevalence of oral Candida colonization was 55%(44/80). The colonization was significantly associated with age of>1 week, male sex, gestational age of <37 weeks, Apgar score of<7, birth weight of <1500 grams, oral mucous pH of <7, systemicantibiotic use, and steroid use by mother. Breastfeeding was aprotective factor. Correlation between variables using Spearmantest revealed correlation coefficient of <0.5. By logistic regres-sion, birth weight of <1500 grams (p=0.04) and systemic antibi-otic use (p=0.01) were significant associated factors of oralCandida colonization, while breastfeeding was a significant pro-tective factor (p=0.03).Conclusion Birth weight of <1500 grams and systemic antibioticuse were significant associated factors of oral Candida colonizationand breastfeeding was a significant protective factor of oral Candidacolonization in neonates